2022
DOI: 10.1037/npe0000161
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy is better than income to predict happiness.

Abstract: Although it is well-known that money or income is related to happiness, little has been learned about the relationship between financial literacy and happiness. The present study used a new financial literacy measurement involving the index of homo economicus (the average of financial knowledge, financial capacity, and financial management values), and the index of homo sociologicus (the average of financial ethics and wealth values), based on the triarchic theory. The aims were to explore the mediation or mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Q. Xin, Zhang, et al, 2018). Moreover, with respect to the predictive validity of these two factors, a recent study found that both the HSI and HEI played independent and vital roles in enhancing happiness (Xiao & Xin, 2022), suggesting that these two factors are distinct but complementary. Therefore, we calculated the HEI using the average score of the three tests’ sum totals (financial knowledge, financial capacity, and financial management values).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Q. Xin, Zhang, et al, 2018). Moreover, with respect to the predictive validity of these two factors, a recent study found that both the HSI and HEI played independent and vital roles in enhancing happiness (Xiao & Xin, 2022), suggesting that these two factors are distinct but complementary. Therefore, we calculated the HEI using the average score of the three tests’ sum totals (financial knowledge, financial capacity, and financial management values).…”
Section: Methodsmentioning
confidence: 99%
“…Financial literacy has been shown to boost happiness and economic confidence, inhibit household overindebtedness, increase retirement planning, and enhance wealth accumulation (Behrman et al, 2012; Bucciol et al, 2021; Sachse et al, 2012; van Rooij et al, 2011; Xiao & Xin, 2022). Given the economic importance, a burgeoning body of the literature has explored how financial literacy is subject to institutional factors, such as poverty, unemployment, and human capital on the regional level (Cucinelli et al, 2019; Cupák et al, 2021; Jappelli, 2010; Lachance, 2014; Li et al, 2022).…”
Section: Financial Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has established that priming individuals to contemplate money or engaging in market activities leads to more unethical and individualistic behaviours and less prosocial behaviours (Falk & Szech, 2013; Vohs et al, 2006; Zhang & Xin, 2019). By considering evidence of the two conflicting views, we have found that there is more evidence suggesting the negative effects of the market mindset (Xin et al, 2022; Xin & Yang, 2023). Also, the majority of studies demonstrating the positive role of the market mindset in prosocial behaviour are predominantly correlational rather than causal in nature, thereby prohibiting the elimination of the influence of other variables (Xin, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Even so, many people are often reluctant to engage in financial activities such as stock and fund investments, credit spending, and debt management. This phenomenon has been explained by many economists and psychologists, who contend that people's subjective and objective financial knowledge, their perception regarding the complexity of financial decisions, and their unique personality traits are significant factors for individuals' reluctance to manage their finances [2][3][4][5]. However, researchers have neglected the influence of contextual anxiety on financial management behavior in financial activities.…”
Section: Introductionmentioning
confidence: 99%